The Study of Genetic Diversity and Relationships on Carica sp. by Means of Random Amplified Polymorphic DNA (RAPD) Analysis - Ahmad Satori; Sriani Sujiprihati; , Sobir (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2002)
The genus of Carica comprises 21 species, among them three species have been domesticated and cultivated. They are Carica papaya, Carica candamarcencis and Carica monoica. In Indonesia, two species have been cultivated viz. Carica papaya and Carica candamarcencis. In this study, four accessions of Carica papaya species and one accession of Carica candamarcencis species were analyzed using RAPD technique. We successfully amplified a total I of 40 fragments from these DNA genome by using 6 random primers with GC bases content:::: 60% of each primer. The number of fragments of each primer ranged from 5 to 8 averaged 6.7 fragments per primer. Out of total fragments, 90% showed as polymorphic ranged from 5 to 8 on average 6 fragments per primer. A dendogram based on the UPGMA- link method using Nei and Li similarity and Principal Component Analysis (PCA) plot separated the accessions into two main groups, the Carica papaya species on the one side and the Carica candamarcencis species on the other side. The result demonstrated that RAPD analysis was able to reveal genetic difference between Carica papaya and Carica candamarcencis species, as well as genetic diversity in Carica papaya species.